Osteomyelitis within the SUS: analysis of the epidemiological profile, cost of hospitalization, average length of stay and mortality in the last 5 years (Research, Society and Development, 2023)
Osteomyelitis is an infectious and inflammatory bone process caused by pathogenic microorganisms, among which Staphulococcus aureus stands out. Given this context, the objective of this study is to analyze the epidemiological profile, the average cost and mortality of osteomyelitis in Brazil over the last 5 years. This is an epidemiological, retrospective and quantitative study carried out using secondary data. In the analyzed period, 71,866 hospitalizations for osteomyelitis were recorded in Brazil. With regard to geographic regions, the largest number of hospitalizations is concentrated in the Southeast region. Regarding age group, patients between 50 and 59 years old were the most affected. Regarding biological gender, males predominated, totaling 51,176 admissions. Among the Brazilian macro-regions, the southern region had the highest average cost of hospitalization for osteomyelitis. The average hospital stay for osteomyelitis, in the period studied, was around 8.4 days in Brazil. And, finally, the mortality rate remained between 1.30, with the year 2020 having the highest mortality rate with 1.63. This research demonstrates that osteomyelitis is a public health problem, subject to early diagnosis and preventive care.